Planificación tributaria para la empresa “corporación ZEN210 S.A.S.” cantón Quito provincia Pichincha 2023. - Vega Vega, Viviana Alexandra (2023)
The project was carried out using information obtained from the ZEN210 S.A.S Corporation and the Internal Revenue Service, having in the Corporation fines generated by declaration delays, lack of identification to which regime it belongs and ignorance of tax incentives due to the fact that there is no accountant. permanently established, so these functions are covered by the accounting assistant who is within the entity for 3 months, with the objective of "Designing a Tax Planning that allows minimizing the tax burden and compliance with the Corporation's tax obligations ZEN210 S.A.S Quito canton, Pichincha province in the year 2023”. The methodology applied was quantitative, the methods used were deductive and analytical-synthetic which allowed the analysis of the information collected from which the essential points for the development of the project and its proposal were established. The field investigation allowed the approach to the entity, the technique was the survey and the documentary review through which physical information, knowledge of the entity, and its operation are obtained. Finally, the benefit that the entity obtains with the Tax Planning Design is the decrease in the amount to be paid for income tax, by 6,85%, unlike the declaration without implementing this tool.